Improving the Quality of Print Media Learning with Press Screening Tech-niques Through Teaching Books - Masnuna; Mahimma Romadhona (Nusantara Science and Technology Proceedings, 2020)
The purpose of this study is to compile a textbook for Visual Communication Design 2 in the Visual Communication Design study program. This course discusses the logo as a visual identity and its implementation in print media using the screen-printing press technique. The research method uses two stages, namely the creation stage and the publication stage. The creation stage includes pre-production, production, and post-production, while the publication stage includes registration of book publishing and book releases. The result of this research is a textbook entitled "Improving the Quality of Learning in Print Media with the Screen-Printing Press Technique". This book contains the process of implementing the results of the illustration of the East Java UPN “Veteran” souvenir design into the DKV media using the Press screen printing technique. The selection of screen-printing techniques is based on the techniques used in the previous research entitled "Visual Design and Souvenir Products of the" Veteran "National Development University of East Java as the Identity of the State Defense Campus". This research concludes that this textbook can be used as the main textbook for DKV 2 courses and as a reference book for several subjects such as DKV 2, Graphic Method, DKV 1, DKV 4, DKV 5, and Final Projects. Besides, this book can also be a reference book for the community in the souvenir production process using the screen-printing press technique.